ANALYSIS OF RUSSIAN FACTORS SUPPORTING NICOLAS MADURO IN THE VENEZUELAN CRISIS FROM ALEXANDER WENDT'S CONSTRUCTIVIST PERSPECTIVE - Kurniati, Endah; Aulia, Jamal Din (SIYAR Journal, 2024)
The crisis happening in Venezuela is a humanitarian crisis that affects political instability and local economics. This economic crisis is caused by reducing the cost of oil supply. Besides, the political crisis began with internal problems between the government and the opponent, exacerbating the situation. It brings attention to developing countries to get into this crisis dynamic, such as Russia. In Venezuela's crisis, Russia offered material support and morality to Nicolas Maduro's government. Thus, Russia attempts to support Maduro from international claims. This research intends to analyze the reasons behind Russia's supporting Nicolas Maduro in the Venezuela Crisis by using the constructivism theory of Alexander Wendt. Based on research results, showed 3 variables that explain Russia's involvement in the Venezuela crisis. Firstly, interdependence is related to corporation dependence between Russia and Venezuela. Second, homogeneity, is based on both the same background. Lastly, common fate is based on the same destiny and adversary between Russia and Venezuela.